PENGARUH FILLER SERBUK BATA MERAH DAN ABU SERBUK KAYU JATI TERHADAP KARAKTERISTIK MARSHALL - Novi Nirmala Putri; Shinta Novriani (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
Road pavement really needs a mixture of asphalt that has good durability and stability, because roads have an important role in the transportation system to support economic growth and community mobility. This study aims to analyze the effect of the use of Red Brick Powder and Teak Wood Powder Ash as a substitute for fillers on AC-WC asphalt mixtures. With the increasing amount of red brick powder and teak wood powder ash and has not been utilized optimally, there is a need for innovation in the use of environmentally friendly alternative materials. The method used in this study is Marshall testing to determine the characteristics of the mixture, such as stability, flow, VIM, VMA, and VFA with different filler content variations. The filler variation used in this study was 0%, 5%, 7% with a ratio of 80 : 20. The results showed that the 7% filler variation provided the most optimal mixture characteristics with a VIM value of 4.89% and a VMA of 15.89% which still met the required specifications. In addition, the values of stability, flow, VFA, and Marshall Quotient are also within the standard limits. Based on these results, red brick powder and teak wood ash have the potential to be used as filler alternatives to AC-WC mixtures that are more environmentally friendly.